Peran Kepala Desa dalam Pembangunan Infrastruktur Jalan di Desa Kariango Kecamatan Lembang Kabupaten Pinrang - Wildasari, Wildasari; Setiawati, Budi; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to find out the role of the Village Head in the construction of road infrastructure in Kariango Village, Lembang District, Pinrang Regency. This study used qualitative research. Data collection techniques were observation, interviews with a number of informants. Data analysis used an interactive analysis model. The results of this study showed that the role of the village head in infrastructure development on village roads was good enough but needed to be improved to be more optimal, this was seen from the aspects of (1) Planning, (2) Implementation ,. (3) Supervision and monitoring. Supporting factors in this activity, there was participation and support from the community, sufficient regional budget funding to carry out development, and regulations provided. While the inhibiting factors were the lack of maximum supervision and monitoring of infrastructure development, then the weather and heavy terrain made it difficult to process infrastructure development and a long time, as well as more expensive development materials.